Turn taking strategies used by Halima Aden and The Host In The Talk show ' Embracing Ambition With Halima Aden ' - Irfa Luthfia Rahmani (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2022)
et,1/adil,c.1